Palliative surgery for advanced gastric cancer: Partial gastrectomy using the inverted laparoscopic and endoscopic cooperative surgery method. (2018) - Takechi, Hitomi; Fujikuni, Nobuaki; Takemoto, Yuki; Tanabe, Kazuaki; Amano, Hironobu; Noriyuki, Toshio; Nakahara, Masahiro
Highlights: We performed partial gastrectomy with LECS as palliative treatment. It was an invasive gastric cancer, but the patient had many comorbidities. LECS was successfully used as minimally invasive palliative treatment. Abstract: Introduction: Laparoscopic and endoscopic cooperative surgery (LECS) is a minimally invasive hybrid procedure that facilitates the precise dissection of gastrointestinal malignancies. We report the use of LECS as palliative treatment for a patient with advanced gastric cancer at a high risk due to comorbidities. Presentation of case: A 68-year-old woman with general malaise was admitted to the hospital and received multiple transfusions for anemia. Endoscopy examination detected an ulcerative lesion in the stomach. She was at high risk due to comorbidities including liver cirrhosis (Child-Pugh score B), aortic stenosis, and coronary artery stenosis requiring operative treatment. Discussion: Imaging revealed no evidence of metastasis. We resected the tumor using LECS to control bleeding. Postoperatively, there were no short-term complications, and there was no recurrence during 6-month follow-up. Conclusion: LECS as palliative treatment may be a viable option for high-risk patients with advanced gastric cancer.